Additional Criteria For Assessing the Effectiveness of Anesthesia in the Process of RPO (Reconstructive Plastic Surgery) In Patients with Post-Burning Contractures of the Face, Neck and Chest (Texas Journal of Medical Science, 2022)
56 patients aged 16 to 50 were under the experience of reconstructive plastic surgery for postburn contractures of the face, neck and chest. According to the anesthetic manual we used, the patients were divided into 2 groups: in the first (1) group - 27 patients (48.2%) used regional anesthesia (blockade of the cervical plexus and 3 branches of the trigeminal nerve). In the second (2) group of 29 patients (51.8%), reconstructive plastic surgery (RPS) was performed under the conditions of total intravenous anesthesia with benzodiazepines, ketamine, fentanyl with myoplegiaarduan in standard age dosages. Oxygen pressure in the soft tissue (PTKO2) of the operated area was examined using a Clark-type transducer using percutaneous contact polarography. The temperature was measured with an electric thermometer with fixation of the central T1C (oral cavity) and peripheral T2C (subclavian region), as well as the affected area T3C. Compared temperature gradients of the flaps at the stages in the groups indicate (indirectly) a microcirculation with regional anesthesia better than TVA. Our obtained results according to the data of thermometry of the flaps at the stages of surgical intervention are quite consistent with those changes in oxygen tension in the tissues of the flap (PTKO2-) in the patients examined by us. This resultsare less complicated in the operated tissues rather than other proven anesthesia methods when using regional anesthesia.